DESIGN AND IMPLEMENTATION OF QUASI-YAGI ANTENNA WITH LARGE VERTICAL APERTURE RADIATION PATTERNS FOR SECONDARY SURVEILLANCE RADAR APPLICATIONS - Rafi Armandsyah, Hadiyan
Secondary surveillance radar system requires being able to capture targets that are far away as well as targets that are close with high elevations. Secondary surveillance radar must also be able to reduce the reflection effect from the ground surface below the radar. The secondary surveillance radar antenna has a standard elevation radiation pattern, namely a large vertical aperture, to meet this need. In this thesis, an 8-element vertical array quasi-Yagi antenna is designed using a power combiner with the distribution of the Woodward-Lawson algorithm to obtain a large vertical aperture elevation profile. The antenna is fabricated on flame retardant-4 substrate with dimensions of 1.1 m x 0.3 m. The choice of quasi-Yagi antenna has an impact on wide bandwidth, which is more than 100 MHz according to the needs of secondary surveillance radar. At the interrogation working frequency of 1030 MHz, a return loss of 18.59 dB was obtained. Meanwhile, at the reception frequency of 1090 MHz, the return loss is 12.73 dB. The gain of the unit antenna is more than 20,76 dBi already meets the technical specifications of the secondary surveillance radar. The elevation profile obtained in the measurement already shows the large vertical aperture profile according to commercial products. At 1030 MHz the beam width is slightly wider, while at 1090 MHz the beam width is narrower.